2023
DOI: 10.2196/44206
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Patient and Public Involvement in the Development of Real-World Digital Technology Solutions: Tutorial

Alison Keogh,
Ríona Mc Ardle,
Mara Gabriela Diaconu
et al.

Abstract: Although the value of patient and public involvement and engagement (PPIE) activities in the development of new interventions and tools is well known, little guidance exists on how to perform these activities in a meaningful way. This is particularly true within large research consortia that target multiple objectives, include multiple patient groups, and work across many countries. Without clear guidance, there is a risk that PPIE may not capture patient opinions and needs correctly, thereby reducing the usef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…The use of sensors allowing to measure several gait parameters, beyond step count, may enhance the precision of mobility evaluations, offering insights critical for personalized healthcare strategies and better understanding of mobility-related disease progression or fall prediction. Within Mobilise-D, patient and public involvement and engagement (PPIE) activities have been developed to ensure that the technology proposed will be inclusive, clinically relevant and responding to the needs of the included groups (56).…”
Section: The Opportunity Of Digital Pro Measures (E-health) -Wg3mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of sensors allowing to measure several gait parameters, beyond step count, may enhance the precision of mobility evaluations, offering insights critical for personalized healthcare strategies and better understanding of mobility-related disease progression or fall prediction. Within Mobilise-D, patient and public involvement and engagement (PPIE) activities have been developed to ensure that the technology proposed will be inclusive, clinically relevant and responding to the needs of the included groups (56).…”
Section: The Opportunity Of Digital Pro Measures (E-health) -Wg3mentioning
confidence: 99%
“…While studies of different durations have demonstrated that sustained adherence to smartphone-based assessments can be achieved by a majority of participants in a supervised research context, reports from naturalistic settings have shown varying patterns of app usage over a 12-week period, overall indicating that user engagement can significantly drop off as time progresses. In a broader market context, retention rates reveal that within 90 days, healthcare apps retain only 31% of their users, and this figure decreases further over the course of a year (55,56).…”
Section: Smartphone-enabled Mobile Health: the Promise And Challenges...mentioning
confidence: 99%
“…We have extensive evidence of working alongside patients in the development of digital health technologies to monitor various conditions including knee replacement rehabilitation [17], heart failure self-management [20,35], and real-world digital mobility outcome measures [41]. We have engaged with patients across each of the domains of patient and public involvement (PPI) in our work (https://www.nihr.ac.uk/documents/briefing-notesfor-researchers-public-involvement-in-nhs-health-and-social-care-research/27371 [accessed on 15 December 2023]), mostly within the Mobilise-D consortium, a public-private partnership which has developed digital mobility outcome measures of real-world walking across multiple patient cohorts.…”
Section: Lessonmentioning
confidence: 99%
“…We have engaged with patients across each of the domains of patient and public involvement (PPI) in our work (https://www.nihr.ac.uk/documents/briefing-notesfor-researchers-public-involvement-in-nhs-health-and-social-care-research/27371 [accessed on 15 December 2023]), mostly within the Mobilise-D consortium, a public-private partnership which has developed digital mobility outcome measures of real-world walking across multiple patient cohorts. This has led to the identification of PPI recommendations [41], changes to protocols, public facing dissemination activities, and more (https://youtu.be/qTazIpSC4DU?si=WwKYSKY2xBu2J2pe [accessed on 10 January 2024]; https://youtu.be/hherCpNiKLw?si=01E5EwPM2ww-xmc_ [accessed on 1 June 2024]; https://youtu.be/3FwD9XZynHo?si=nHSkxjqQpQxGJDBp [accessed on 15 December 2023]; https://youtu.be/Y_rfqCROIDQ?si=pRI2Fq0O49Bm5B4M [accessed on 15 December 2023]; https://mobilise-d.eu/ppag-activities-and-contributions/ [accessed on 15 December 2023]). Engaging meaningfully in this user-centred design approach means that the solution might not eventually be the one that was originally envisaged, it might not be a net positive for all types of users, nor might it be simply a digitisation of the current care pathway.…”
Section: Lessonmentioning
confidence: 99%